A construção do conhecimento na disciplina de arte: práticas pedagógicas por meio das tecnologias móveis sem fio - Raach, Adriana Beatriz Pacher (2016)
This dissertation looks into the construction of knowledge in the pedagogical practice in Art through mobile wireless technologies. The study is inserted in the Line of Cultural Research, Languages and Technologies in Education, of the Program of Post-Graduate Studies in Education, of the University Center La Salle - UNILASALLE. As a research problem a question has been raised: How does the construction of knowledge in Art through pedagogical practices that use mobile wireless technologies happen? The general objective is to analyze the process of constructing knowledge in Art, by pedagogical practices, emphasizing the use of mobile wireless technologies. The theoretical study in which this research is grounded comprises: Piaget and Freire (construction of knowledge and teaching practice); Morais and Barbosa (teaching practice); Santaella (mobility and wireless mobile technologies); and Silva (hybrid classrooms). This way, teaching practices that provide reading, contextualization and artistic work with mobile wireless technologies were developed, in Barbosa’s triangular approach. The methodology of research consists in the study of case, being the analysis of data qualitative. The research field was held in a private school of Porto Alegre / RS, where the writer of this work taught Art classes. As a reflection on the research problem, it was noticed that the construction of knowledge in Art occurred from the cognitive action (art making), the relationship between subject and object (exploration, research), through analog and digital resources; in the interaction among students, teacher and environment; and through curiosity, reflection and criticism. Students, however, had difficulty in: understanding the digital resources in the context of educational processes and their usage in artistic activities and, performing actions of cooperation in group activities. Thus, it was emphasized the evidence of the dominance of traditional educational model, not only in the school context and the action of teachers, but also in the students’ attitude. Therefore, it is important to bring back the triangular approach in teaching practices in the art classes by introducing mobile wireless technologies.